Character Education in Islamic Education at Madrasah School Level - Sirait, Ibrahim (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: Character education is an essential part of school work, but so far it has received little attention. Schools should not only be obliged to increase academic achievement, but also be responsible for shaping the character of students. Methodology: This research uses the literature study method which relies on bibliographic sources from books and articles in scientific journals related to the subject matter, reading data with the thoughts of experts with a constructive approach and interpretation of the main content. Main Findings: Character is developed through the knowledge stage, leading to habituation. Where character is not only based on knowledge, someone who has knowledge about goodness is not necessarily able to act according to his knowledge. So if you are trained to do good, character is not limited to knowledge, character goes deeper into the realm of emotions and personal habits. The Qur'an as a moral reference. Where the Al-Qur'an functions to convey a guiding treatise for organizing attitudes and behavior that must be carried out by humans and where the character education model based on the Al-Qur'an which has been explained in the previous chapter needs to be reviewed, understood and synchronized so that it is easier to understand in learning at school madrasah level Novelty/Originality of this study: The originality of this research lies in its focus on exploring the potential of character education in Islamic education and its significance in the current context. Although there are many studies on character education and Islamic education separately, research that systematically explores the integration of these two fields in a contemporary context is very limited.